Introduction to the Qur'an - Watt, William Montgomery; Bell, Richard (The New Edinburgh Islamic Surveys : NEIS, 2022)
Surveying the life, aims, character and inspiration of Muhammad, this classic introduction explains the history, form and chronology of the Qur'an, and gives the views of Muslim and Occidental scholars.